Upaya Kepala Sekolah dalam Mengembangkan Kompetensi Guru - Muhammad Duratunnasihin; Sukatin; Mardiyana; Putri Nurhaliza; Fahmi; Sindi Eka (Medan Resource Center, 2021)
This study aims to determine the efforts of school principals in developing teacher competence to improve the quality of education in Indonesia. This research is a descriptive research with a qualitative approach. The subject of this research is the principal. The technique used in data collection is interview, observation, and documentation. The validity of the data was tested by triangulation of sources and triangulation of techniques. The data were analyzed using the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the principal's function as an educator is to create a conducive school climate, provide advice to school residents, provide encouragement to education staff and implement interesting learning models. As a manager, the principal is able to deal with various problems at school, thinks analytically, conceptually, always tries to be an intermediary in solving various problems. The principal as an administrator has a close relationship with various administrative management activities that are recording, compiling, and documenting all school programs. As a supervisor, the principal supervises the work carried out by education personnel. As a leader, he must be able to provide guidance and supervision, increase the willingness and ability of educational staff, open two-way communication and delegate tasks. as an innovator, it is necessary to have the right strategy to establish a harmonious relationship with the environment, seek new ideas, integrate every activity, set an example for education staff and develop innovative learning models. As a motivator, the principal has the right strategy to motivate education staff in carrying out various tasks and functions.